Fuego, grito, luna : Federico García Lorca. Poema en tres letras / de Fina de Calderón, [textos de Federico García Lorca... (et al.); obra gráfica... Rafael Alberti.... (et al.)] - García Lorca, Federico (1898-1936) Alberti, Rafael (1902-1999); Calderón, Fina de (1927-2010)
Descripción basada en la cub.